CALCULATION METHOD FOR DETERMINATION OF ADHESION LEVEL OF COMPOSITE REINFORCEMENT WITH CONCRETE - Firsov, Р.; Zolotov, S.; Nadtochiy, S. (Municipal economy of cities. Series: «Economy science», 2023)
The scientific work is devoted to the interaction process of concrete and composite reinforcement, which is characterized by “adhesion-slip” dependence. It is known, that composite reinforcement does not behave in the same way as traditional steel reinforcement, because in some cases their mechanical properties differ significantly. CFRP/FGRP/BFRP products have higher strength, but a lower modulus of elasticity, so direct replacement of steel with such reinforcement is not always possible according to many constructional requirements. Adhesion forces create a complex stress-strain condition in concrete interacting with reinforcement. This condition leads to the distribution of loads along the axis of reinforcement, and, as a result, the longitudinal forces on reinforcement become variable along the entire length of the rod. A detailed analysis of the existing approaches to the problem of adhesion level of concrete and composite reinforcement is performed in article. It was determined that the complex multiparameter state of the interaction of concrete and composite reinforcement is characterized by the corresponding curves of “adhesion-slip” dependence, which can be obtained by two experimental methods (beam test method and direct pull-out test method). A theoretical research of the adhesion level of concrete and composite reinforcement (beyond the limits of cracks formation) was carried out, connected with the analysis of the distribution of deformations of concrete and reinforcement along the span of the element. Current analysis is based on the determination of a number of differential equations with a step-by-step description of adhesion level problems. The results of research can be used in future during the design and calculation of concrete structures reinforced with different types of composite reinforcement (based on basalt, glass, carbon fibers etc.), however, it is necessary to conduct further experiments into the long-term operation (behavior) of composite reinforcement over time under the influence of various factors, to establish a number of rheological aspects.